Improving Community Knowledge and Skills through Innovation in Utilizing Sorghum Waste as Organic Fertilizer in Batu Layang Village, North Bengkulu Regency - Susilo, Edi; Salamun; Dwi Hermawati; Parwito; Indra Warman; Ina Asitalia; Tila Watil Muslim Meini; Leres Puspitasari; Fitria Yulianti; Shinta Risti Astuti; Rahmat Setiaji; Sanju Diosi Arisca; Mini Asmarita; Iskarnedi; Rita, Wismalinda (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Diversification of local foods is a strategic step in achieving food self-sufficiency and reducing dependence on imports and a single major commodity. However, the dominance of rice as a staple food remains a challenge for national food security. Sorghum (Sorghum bicolor L.) has great potential for development due to its high nutritional content, tolerance to marginal land, and gluten-free properties. However, its utilization in Indonesia is still relatively limited. In Batu Layang Village, Hulu Palik Subdistrict, North Bengkulu Regency, this community service activity targeted farmer groups, PKK, youth, and the general public. The Participatory Rural Appraisal (PRA) method was applied through socialization, training, and demonstration of sorghum waste processing, product downstreaming assistance, evaluation, and marketing strategy strengthening. The results of the activities showed a significant increase in the knowledge and skills of the community, particularly in processing sorghum waste into high-quality organic fertilizer. The evaluation showed increased post-harvest capabilities and a high level of participant satisfaction. In addition to producing economically valuable products, this program also broadened the community's knowledge of food diversification and encouraged forming joint business groups in the future.